A Study on Arsenic Speciation in Korean Oyster Samples using Ion Chromatography Inductively Coupled Plasma Mass Spectrometry. (January 2015) - Nam, Sang‐Ho; Cui, Sheng; Oh, Hae‐Joon; Min, Hyung‐Sik; Lee, Joung Hae
<x xml:space="preserve">Abstract</x> The qualitative and quantitative analysis of the different arsenic species in Korean oyster samples was performed to provide the vital information of food safety of the marine sample in terms of the arsenic species. Korean marine samples, oysters, were obtained from nine sites in the western and southern areas of South Korea. Inductively coupled plasma mass spectrometry (ICP‐MS) was used to measure the total arsenic. The different arsenic species in the oyster were separated by ion chromatography (IC), and then detected by ICP‐MS. Extraction of arsenic species was performed with the mixed solvent of the methanol:water (3:1). The extraction efficiency of arsenic species (the ratio of total amount of the different arsenic species to the total arsenic in the oyster) for nine oysters was approximately 73–81%. The major arsenic species in the oyster was arsenobetaine, and its concentration in the samples was in the range of 7–16 mg/kg that was more than 90% of the total organic arsenic in the oyster. As(III) was not generally detected while the trace As(V) was detected in most oysters.